Kesulitan konsep materi keanekaragaman suku bangsa dan budaya pada pembelajaran daring peserta didik kelas IV sekolah dasar - Sari, Awanda Anindita; Istiyati, Siti; Kamsiyati, Siti (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2022)
The aims of this study is to describe the form of difficulty in internalizing concept of cultural ethnic diversity and technical difficulties in implementing the online learning process experienced by fourth grade elementary school students. This research is a qualitative research (case study approach). The subjects of this study were students, teachers, and parents. Data was collected by means of interviews, questionnaires, and document studies. The validity test technique used is triangulation of sources and techniques. Analysis of the data using the analysis model of Miles and Huberman. The results of this study are as follows. First, the form of difficulty in internalizing the concept is the identification of forms of local cultural diversity and providing examples of respect for this diversity caused by eye disorders, lack of interest and motivation, lack of parental attention, home atmosphere is not conducive, the implementation of learning is not in accordance with the lesson plan, and the ability of teachers to diagnose children's learning difficulties is low. Second, technical difficulties in the implementation of online learning are inadequate learning tools and internet quota, low tech ability, teachers don’t use learning models, and teachers use inappropriate learning methods that don’t facilitate online student activity.